2018
DOI: 10.1155/2018/4636783
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 2 and Peroxisome Proliferator-Activated Receptor γ Gene Polymorphisms in Association with Diabetes Susceptibility in Chinese Han Population with Variant Glucose Tolerance

Abstract: Objective To investigate the association of polymorphisms in uncoupling protein 2 (UCP2) and peroxisome proliferator-activated receptor (PPARγ) with glucolipid metabolism in Chinese Han population. Methods Five hundred eighty-nine subjects were divided into normal glucose tolerance (NGT) group (n = 198) and abnormal glucose tolerance group (n = 358). HbA1c, blood lipid profile, plasma glucose, and insulin were determined. Insulin sensitivity (HOMA-IR and Matsuda index (ISIM)) and insulin secretion indexes (HOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Previous research with genotype analysis and further clinical features showed that subjects with the genotype TT rs649446 or subjects with AA rs7109266 genotype on UCP2 had higher HOMA-IR and HOMA-β, subjects with AA genotype rs7109266 also had a higher waist-hip ratio high, which suggests that subjects with TT genotype rs649446 or subjects with AA genotype rs7109266 are more prone to develop insulin resistance [18]. Previous studies have shown that human islet with GA genotype UCP2-866 polymorphism has decreased glucose-stimulated insulin secretion compared with GG.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research with genotype analysis and further clinical features showed that subjects with the genotype TT rs649446 or subjects with AA rs7109266 genotype on UCP2 had higher HOMA-IR and HOMA-β, subjects with AA genotype rs7109266 also had a higher waist-hip ratio high, which suggests that subjects with TT genotype rs649446 or subjects with AA genotype rs7109266 are more prone to develop insulin resistance [18]. Previous studies have shown that human islet with GA genotype UCP2-866 polymorphism has decreased glucose-stimulated insulin secretion compared with GG.…”
Section: Discussionmentioning
confidence: 96%
“…The I allele and DI genotype are more common in diabetic retinopathy among the Chinese population . The II and DI genotypes are associated with a higher risk of proliferative diabetic retinopathy and the DI genotype is associated with a higher risk of non‐proliferative diabetic retinopathy . In an Iranian study, the 45‐bp I/D polymorphism of the UCP2 gene is shown to be associated with the metabolic syndrome, which is being recognized as a risk factor for insulin resistance .…”
Section: Ucp2 and Diabetesmentioning
confidence: 98%
“…There are fewer reports on the 3 0 -UTR 45-bp I/D polymorphism in diabetes. The I allele and DI genotype are more common in diabetic retinopathy among the Chinese population [19,20]. The II and DI genotypes are associated with a higher risk of proliferative diabetic retinopathy and the DI genotype is associated with a higher risk of non-proliferative diabetic retinopathy [19,20].…”
Section: Ucp2 and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to obtain more direct evidence for the involvement of UCP2 in diabetic retinopathy, several groups have carried out GWAS studies and have identified a significant linkage between several UCP2 polymorphisms and the diabetic retinopathy phenotype [ 90 , 91 , 92 ]. Interestingly, the association was stronger with the more severe, proliferative forms of the disease.…”
Section: Ucp2 and Retinal Degenerationmentioning
confidence: 99%